Character Education and Related Trend Variables - Sumiati Side; Vika Puji Cahyani (Universitas Cokroaminoto Palopo, 2025)
Various studies have been conducted to examine the effectiveness of character education in various contexts, including schools, families, and communities. However, as the scope of studies on character education has expanded, there is a need to understand how research trends in character education have developed over time. This study aims to analyse bibliometric trends in character education variables using data from scientific publications available in academic databases. This study uses a qualitative approach by combining bibliometric methods and systematic literature reviews (SLR) to analyse research trends and understand the importance of character education in learning. The results show that character education plays a crucial role in shaping students' morals and ethics from an early age through the support of the curriculum, schools, families, and communities, as well as the application of cultural values. Character education is an important aspect in the formation of individual personality. Character education can serve as a means of building environmental awareness among learners. Variables closely related to character education include Character Strengths, Virtue Ethics, Positive Education, Critical Thinking, Affective and Social Outcomes, Environmental Consciousness.